(untitled) (Discourse of Law and Administration, 2022)
The aim of the publication is to present several postulates de lege ferenda relating to the complaint against the ruling of the court referendary after the changes introduced by the Act of 4.07.2019. The aforesaid amendment changed the structural assumptions of this appeal, which, however, need to be modified to some extent, such as amending the provision of Article 39822 § 1 of the CPC by assuming that the appeal is entitled to the enumerated decisions included in the wording of Article 3942 but also in Article 3941a of the CPC, and issued by a court referendary in appeal proceedings. Moreover, a court referendary should be given the power to dismiss a complaint against a decision made by him/her, and the catalog of decisions under Article 39823 § 1 of the CPC should be expanded to include decisions declaring judgments by court referendaries to be legally binding and reviewing judgments which, if appealed against, do not render them invalid, but only suspend their enforceability.